THE INFLUENCE OF ALLOYING ELEMENTS AND IMPURITIES CONTAINED IN ALUMINA MATRIX QUARTZ-CONTAINING COMPOSITIONS, ON THE RECOVERY PROCESS FOR THE SYNTHESIS OF SILICON SILUMIN - A. V. Arabey (Литьë и металлургия)
The main regularities of influence of the main alloying elements and impurities, contained in the components of alyumomatrix silica containing compositions, on recovery of silicon and its oxides in the melt aluminum while producing synthetic silumin are presented.